The Role of Simple Accounting in Promoting Accountability and Sustainability of SMEs in Pesantren Environments - Hamzah, Amir; Rahmawati, Teti (Universitas Ahmad Dahlan, 2025)
This study investigates the influence of simple accounting records, accounting literacy, access to capital, and the use of accounting technology on the accountability and sustainability of small and medium enterprises (SMEs) operating within pesantren environments in Kuningan Regency. Employing a quantitative research design with a survey methodology, data were collected from 152 SME owners or managers engaged in financial decision-making, selected through purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The empirical findings indicate that all examined factors, namely simple accounting practices, accounting literacy, capital access, and the use of accounting technology, positively contribute to enhancing both accountability and sustainability among SMEs in the pesantren context. These results underscore the importance of strengthening financial literacy and embracing technological tools to foster sustainable business practices. As one of the pioneering studies to explore the intersection of accounting practices and SME sustainability within Islamic boarding school (pesantren) environments, this research offers novel insights into the adaptation of financial management strategies to culturally and institutionally distinct settings.